1999
DOI: 10.1152/jn.1999.81.3.1123
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Dependent Sodium and Calcium Currents in Acutely Isolated Adult Rat Trigeminal Root Ganglion Neurons

Abstract: Voltage-dependent sodium (INa) and calcium (ICa) currents in small (<30 microM) neurons from adult rat trigeminal root ganglia were characterized with a standard whole cell patch-clamp technique. Two types of INa showing different sensitivity to tetrodotoxin (TTX) were recorded, which showed marked differences in their activating and inactivating time courses. The activation and the steady-state inactivation kinetics of TTX-resistant INa were more depolarized by about +20 and +30 mV, respectively, than those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 28 publications
4
20
0
2
Order By: Relevance
“…Pioneering studies showed that tetrodotoxin (TTX) and local anesthetic bupivacaine application on the IO nerve did not affect barrelette formation in the rat PrV (Henderson et al, 1992). More recent studies uncovered that trigeminal ganglion cells have TTXresistant Na ϩ and voltage-dependent Ca 2ϩ channels that produce Ca 2ϩ spikes (Kim and Chung, 1999;Cabanes et al, 2002). Furthermore, TTX or bupivacaine does not appear to block spontaneous activity of trigeminal ganglion cells Shoykhet et al, 2003).…”
Section: Physiological Evidence For Activity-dependent Plasticity In mentioning
confidence: 99%
“…Pioneering studies showed that tetrodotoxin (TTX) and local anesthetic bupivacaine application on the IO nerve did not affect barrelette formation in the rat PrV (Henderson et al, 1992). More recent studies uncovered that trigeminal ganglion cells have TTXresistant Na ϩ and voltage-dependent Ca 2ϩ channels that produce Ca 2ϩ spikes (Kim and Chung, 1999;Cabanes et al, 2002). Furthermore, TTX or bupivacaine does not appear to block spontaneous activity of trigeminal ganglion cells Shoykhet et al, 2003).…”
Section: Physiological Evidence For Activity-dependent Plasticity In mentioning
confidence: 99%
“…Later studies documented that TG cells have TTX-resistant Na ϩ channels and voltage-dependent Ca 2ϩ channels that produce Ca 2ϩ spikes (Kim and Chung, 1999;Cabanes et al, 2002). Spontaneous activity in the TG is also not blocked by TTX or bipuvicaine (Shoykhet et al, 2000(Shoykhet et al, , 2003Minnery et al, 2003).…”
Section: Neural Activitymentioning
confidence: 99%
“…Таким чином, зменшення концентрації кальцію в зовнішньоклітинному розчині приз водить до модуляції електричної актив-ності нейронів ГТН. Пригнічення горба на фазі реполяризації та зниження порогу гене-рації свідчить про наявність низькопорогових та високопорогових кальцієвих каналів [20]. Зміни у слідовій гіперполяризації та частот-них характеристиках вказують на активність кальційзалежних калієвих каналів [21].…”
Section: результати та їх обговоренняunclassified
“…Така різниця додатково доводить, що імпульсній активності ноцицепторів властива нечутливість до ТТХ [11]. Експресія в мембрані потенціалзалежних кальцієвих та ТТХ-резистивних натрієвих каналів може бути причиною генерації відповідей за наявності ТТХ [11,20]. Отримані результати збігаються з даними експериментів in vivo на нейронах ГТН миші, у яких спостерігалося повне або часткове пригнічення імпульсної активності за наявності ТТХ у сомах Aδ-волокон.…”
Section: результати та їх обговоренняunclassified